Partisipasi aktif dalam ibadah online sebagai tanda persekutuan - Pakpahan, Binsar Jonathan (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2022)
This article aims to explain the differences between the online community and fellowship (church) through the dimensions of active participation in online worship. A fellowship is a community of baptized who confessed their faith and are actively involved in their calling. In a local church, members are united by common culture, language, and history. It is feared that online worship carried out during the Covid-19 pandemic will reduce the meaning of fellowship. Through descriptive qualitative method plus observation, with the theory from Alan Rathe and F. Gerrit Immink regarding active participation, this study found three indicators that could help churches prepare their worship to invite active participation as a sign of fellowship. The three indicators are “in” which refers to the common ground, namely initiation in the Triune God; "with" which refers to the congregation's togetherness to follow and participate both in terms of time and ability to interact; and "by" that is doing something together such as singing and responding to the same ritual. AbstrakArtikel ini bertujuan untuk menjelaskan perbedaan komunitas dan persekutuan (gereja) online melalui dimensi partisipasi aktif dalam ibadah secara online. Persekutuan adalah komunitas orang-orang yang dibaptis yang memiliki pengakuan iman, dan terlibat aktif dalam tugas panggilannya. Dalam bentuk gereja lokal, anggota diikat oleh kesamaan budaya, bahasa, dan sejarah. Ibadah online yang dilaksanakan dalam masa pandemi Covid-19 dikhawatirkan akan mengurangi makna persekutuan. Melalui metode kualitatif deskriptif ditambah observasi, dengan teori dari Alan Rathe dan F. Gerrit Immink mengenai partisipasi aktif dalam ibadah, penelitian ini menemukan tiga indikator yang mengukur partisipasi jemaat dalam ibadah. Ketiga indikator itu adalah “dalam” yang merujuk kepada kesamaan landasan yaitu inisiasi dalam Allah Tritunggal; “bersama” yang merujuk kepada kebersamaan jemaat mengikuti dan berpartisipasi baik dari sisi waktu maupun kemampuan berinteraksi; dan “dengan cara” yaitu melakukan sesuatu bersama seperti bernyanyi dan merespons tata ibadah yang sama.